A 1998 Social Accounting Matrix (SAM) for Paraguay - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
The 1998 Paraguay Social Accounting Matrix (SAM) is based on the 1997-98 integrated household surveys, the matrix for intermediate demand by the Central Bank of Paraguay (CBP), the final demand matrix and total supply matrix constructed also by the CBP, tax information for the principal tax payers reported by the Ministry of Finance (MF) disaggregated in different levels, balance of payments statistics and the national accounts bulletin from the CBP. The SAM distinguishes eight sectors of activities times equal number of commodities. These sectors include (1) primary sector (agriculture, livestock, hunting, mining and fishery), (2) manufactured goods, (3) construction, (4) utilities (electricity and water and sewage), (5) transportation, storage and communications, (6) trade, restaurants and hotels, (7) financial services such us banking, insurance, real state and services provided to the firms, and (8) community, social and personal services.